Optimizing temperature parameters for enhanced mineralization process: maximizing CO2 conversion efficiency and stability of formed carbonate minerals - Teoh, Hou Jie (2024)
The escalating global warming crisis, exacerbated by increasing carbon dioxide (CO2) emissions and subsequent greenhouse effects, highlights the urgent need for innovative environmental technologies. Industrial processes, like steel production, greatly add to the buildup of industrial waste, increasing environmental worries and requiring new management methods. In this context, mineralization emerges as a promising method addressing both the mounting industrial waste and the imperative to reduce CO2 emissions. This study investigates the impact of varying temperatures on the mineralization process, utilizing analytical tools such as Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDX), X-ray Diffraction (XRD) analysis, and Thermogravimetric Analysis (TGA) for comprehensive analysis. Through this investigation, temperature parameters for mineralization are optimized, resulting in the maximization of CO2 conversion efficiency and determination of thermal stability in the formed carbonate minerals. Local Electric Arc Furnace (EAF) slags, with particle sizes ranging from 0.8 mm to 2.36 mm and comprising 62.72 % calcium oxide, serve as the primary reacting waste materials. The study encompasses 27 sets of slag samples undergoing mineralization under various simulated conditions, including different CO2 gas concentrations (10 %, 20 %, and 30 %) and humidity levels (40 %, 60 %, and 80 %) at temperatures of 40 °C, 60 °C, and 80 °C. The study achieves a maximum CO2 conversion efficiency of 12.79 %, under experimental parameters of 80 °C temperature, 30 % CO2 gas concentration, and 80 % relative humidity levels. EDX testing demonstrates a positive correlation between temperature parameters and CO2 conversion efficiency, while SEM testing identifies visible crystal structures in the EAF slag samples only at 80 °C mineralization. XRD confirms the presence of calcium carbonate in all samples, with identified polymorphs including 63 % vaterite and 37 % calcite. TGA indicates a 2 % reduction in the sample mass of the carbonate minerals formed when subjected to heating up to approximately 900 °C. In conclusion, this study underscores the pressing need for innovative environmental technologies in combating the escalating global warming crisis.